PERBANDINGAN MODEL MANAJEMEN SALDO KAS PEMERINTAH (STUDI KASUS PADA SALDO KAS PEMERINTAH INDONESIA TAHUN 2009) - Eko Sumando (Badan Pendidikan dan Pelatihan Keuangan - Kementerian Keuangan Republik Indonesia, 2014)
The purpose of this study is to examine the feasibility of the government cash balance management model based on best practice in an article by Yibin Mu (2006), namely : simple management and active management. This study intends to find out which of this two model that are able to generate a lower total cost of holding cash. The Miller-Orr model for cash management are used to simulate the active management model. The result is active management are able to generate lower opportunity cost of holding cash than simple management but generate higher trading cost. Application of active cash balance management model throught the simulation of Miller-Orr model is unable to generate the optimal target cash balance that can minimize the total cost of holding cash.